Interleukin 12 exerts a differential effect on the maturation of neonatal and adult human CD45R0- CD4 T cells. - Shu, U (1994)
It is now recognized that IL-12 plays a predominant role in protective immunity against intracellular pathogens by promoting the development of T helper type 1 (Th1) responses. We here report the unexpected observations that IL-12 exerts differential effects on the maturation of "native" human CD4 T cells isolated from umbilical cord blood or from the blood of healthy adults. After priming in the presence of IL-12, naive cells of adult donors, defined as CD45R0- CD4+ T cells, acquire a Th1 phenotype whereas neonatal cells develop into effector cells producing high levels of IL-4 in addition to IFN-gamma. This effect of IL-12 on neonatal T cells is direct inasmuch as it is observed on highly purified CD4 T cells, however, it is not inhibited by CD8 T cells and natural killer cells. Unstimulated neonatal T cells which have been preincubated with IL-12 before the priming behave like adult T cells and acquire a Th1 phenotype after stimulation in the presence of IL-12. Given that IL-4 is a potent antagonist of Th1 responses, the finding that IL-12 promotes the maturation of neonatal T cells into IL-4 producers may explain the increased susceptibility of neonates to intracellular pathogens and should be taken into account for the development of vaccines to be used in the perinatal period.